MINAT MAHASISWA DALAM BERWIRAUSAHA - Liestan, Liezel Callista; Santony, Louis; Harriyanto, Randy; Putra, Sinar Dharmayana (Jurnal Pengabdian dan Kewirausahaan, 2024)
Entrepreneurship education stands as a cornerstone in shaping the competitive economic landscape of any nation. This study delved into assessing the interest of STIE Ciputra Makassar students in entrepreneurship and gauging their awareness of entrepreneurship education. Utilizing a survey method, the research encompassed the entire student body of STIE Ciputra Makassar. The survey, distributed among 107 students with an average age range of 18-19 years, revealed that nearly 80% harbored aspirations to venture into entrepreneurship. The findings highlighted two pivotal factors influencing entrepreneurial intentions: the affective component (C) and the entrepreneurial environment (E). Conversely, the cognitive component (B) and the behavioral component (A) were identified as factors devoid of significant impact on entrepreneurial intentions. This study underscores the critical role of affective factors, such as passion and drive, alongside the nurturing entrepreneurial ecosystem, in fostering entrepreneurial intentions among students. The high percentage of students aspiring to be entrepreneurs indicates a palpable interest in entrepreneurship within the student community of STIE Ciputra Makassar. Furthermore, the results underscore the importance of incorporating affective and environmental factors into entrepreneurship education curricula to cultivate and enhance students' entrepreneurial aspirations. By addressing these influential factors, educational institutions can better equip students with the necessary skills, mindset, and resources to navigate the complexities of entrepreneurship. In conclusion, this study provides valuable insights into the entrepreneurial landscape among STIE Ciputra Makassar students, emphasizing the need for tailored educational approaches that harness and amplify students' inherent entrepreneurial drive while fostering a conducive entrepreneurial environment.